Computer Information Systems - Analysis and Technologies 10th International Conference, CISIM 2011, Held in Kolkata, India, December 14-16, 2011. Proceedings - Chaki, Nabendu; Cortesi, Agostino (Communications in Computer and Information Science,, 2011)
This book constitutes the refereed proceedings of the 10th International Conference on Computer Information Systems, CISIM 2011, held in Kolkata, India, in December 2011. The 30 revised full papers presented together with 6 keynote taks and plenary lectures were carefully reviewed and selected from 67 submissions. The papers are organized in topical sections on networking and its applications; agent-based systems; biometric applications; pattern recognition and image processing; industrial applications; algorithmic applications and data management; information and network security.